In vitro cell culture system optimization of keratinocytes from oral lichen planus (OLP) patients. (28th November 2016) - Cao, T; Zhang, H; Zhou, L; Wang, Y; Du, G; Yao, H; Wang, Y; Luo, Q; Chen, F; Wang, W; Tang, G
Abstract : Objectives: The aim of this study was to optimize the culture system of keratinocytes obtained from patients with oral lichen planus (OLP) and verify whether this model could simulate the local inflammatory environment of OLP. Materials and methods: Keratinocytes were isolated from 48 patients with OLP and cultured in vitro . The ultrastructure of OLP keratinocytes was observed via electron microscopy. The expression of pancytokeratin and vimentin was determined by immunohistochemistry, and the proliferation of OLP keratinocytes was measured by CCK‐8 assay. Immunofluorescence staining was used to detect TLR4 and NF‐ κ B p65 expression, and the levels of IL‐1 β, IL‐6, and TNF‐ α in the supernatant were measured by ELISA. Results: When seeded in plates precoated with recombinant human type‐1 collagen, keratinocytes isolated from patients who received systemic antifungal treatment and were younger than 40 years were more successful to be cultured in vitro . Characteristic pancytokeratin was expressed in almost all OLP keratinocytes. Compared with normal oral keratinocytes, OLP keratinocytes demonstrated higher levels of TLR4/NF‐ κ B p65 and inflammatory cytokines, including IL‐1 β, IL‐6, and TNF‐ α . Conclusions: We successfully optimized the culture system of OLP keratinocytes, which mimicked the local inflammatory environment of OLP and may be used as a cell model of OLP.